Los organismos incrustantes del Puerto de Mar del Plata - Bastida, Ricardo (1969)
The present paper deals on ecological aspects of the Gastropoda Pulmonata Siphonaria lessoni (Blainville, 18.24) a common member of fouling communities in Mar del Plata’s port (38°08f17" S, 57°31118" w) Populations on colonized panels of an experimental raft were studied along three annual cycles, to determine feeding, habits, growth and those factors that restrict their distribution on floating substratum. Although Siphonaria lessoni is a harmless species as a fouling organism, its grazing on the Algae-belt clears up a part of substratum’s surface, then quickly colonized by really agressive organisms such as Balanus amphitrite.